Desigualdad, instituciones y crecimiento económico en América Latina - Coatsworth, John H. (Pontificia Universidad Católica del Perú. Fondo Editorial, 2012)
Inequality, institutions and economic growth in Latin AmericaThis essay examines three recent historical approaches to the political economy of Latin America’s relative economic backwardness. All three locate the origins of contemporary underdevelopment in defective colonial institutions linked to inequality. The contrasting view offered here affirms the significance of institutional constraints, but argues that they did not arise from colonial inequalities, but from the adaptation of Iberian practices to the American colonies under conditions of imperial weakness. Colonial inequality varied across the Americas; while it was not correlated with colonial economic performance, it mattered because it determined the extent of elite resistance to institutional modernization after independence. The onset of economic growth in the mid to late nineteenth century brought economic elites to political power, but excluding majorities as inequality increased restrained the region’s twentieth-century growth rates and prevented convergence

En el presente ensayo se examinan tres enfoques históricos recientes sobre la economía política del atraso económico relativo de América Latina. Los tres enfoques sitúan el origen del subdesarrollo contemporáneo en instituciones coloniales defectuosas ligadas a la desigualdad. La visión contrastante que se ofrece aquí reafirma la importancia de las limitaciones institucionales, pero argumenta que estas no surgieron de las desigualdades coloniales, sino de la adaptación de las prácticas ibéricas a las colonias americanas bajo condiciones de debilidad imperial. La desigualdad colonial variaba en las Américas; no obstante, no estuvo correlacionada con el desempeño económico y fue significativa porque determinó la extensión de la resistencia de las elites a la modernización institucional de la Independencia. El comienzo del crecimiento económico desde la mitad y hasta fines del siglo XIX llevó a las elites económicas al poder político, pero al excluir a las mayorías, a la par que la desigualdad se incrementaba, restringió las tasas de crecimiento económico de la región durante el siglo XX e impidió la convergencia.
Keywords: Economy; Anthropometric History, Inequality, Heights, Peru, Ethnicity, Regional Inequality; Economía Política; Instituciones Coloniales; Crecimiento Económico; Desigualdad; https://purl.org/pe-repo/ocde/ford#5.02.01